Organizational conflict: "a constructive solution” - González Consuegra, Yamilet (Pensando Psicología, 2010)
This paper describes a research’s results which purpose was to encourage the interpersonal abilities and problemsolving skills of individuals within an organization. A new line of research in Organizational Psychology was started with the design and implementation of the program “Recognizing conflicts in the workplace”, specifically within the communication area. The research methodology implemented is characterized by its flexible design, which allows the necessary adjustments according to the requirements and changes that could possibly arise, using an action-research qualitative approach. The test/re-test procedure was used for the initial diagnostic and later evaluation of the results, concluding that theprogram provided the participants the abilities needed for reducing dysfunctional conflicts from a constructive standpoint, favoring personal development and organizational efficiency.
Keywords: organizational conflict (conflict); conflict resolution strategy (solution); communicative skills (skills); training program (program); typology of the conflict (type)